«Danger: Security»! Securitization Theory and the Paris School of International Security Studies - O. S. Gaidaev (Vestnik MGIMO-Universiteta)
Why does security require to be handled carefully? Can there be too much security? The scholars of the Copenhagen School: O. Wæver and B. Buzan, tackled these questions using the theory of securitization and studying security as a form of social practice. The idea that security should not always be regarded as an absolute good in international politics and threats should not always be objectified is firmly rooted in the constructivist approaches to studying international security. A continuation of these discussions may be found in the theoretical approaches that have been developed for almost fifteen years by the so-called Paris School of international security studies. Unfortunately, one has to admit that although Russian scholars are familiar with these theoretical approaches in general, the existing reviews are still largely superficial. In order to fill this gap, I have attempted to overview and assess the intellectual heritage of the Paris School comprehensively and holistically, turning to the original works of the leading figures within the school: D. Bigo and J. Huysmans. This article continues the series of studies, entirely devoted to the phenomenon of securitization: from the early drafts of the theory towards the modern theoretical concepts.Some of the notions are introduced into the Russian academic use: “domains of insecurity,” “exceptional securitizing,”“diffuse securitizing.”The article focuses on analyzing the theoretical and philosophical underpinnings of the Paris School approach in general and the theory of (in)securitization in particular. It gives a detailed review of the authors’ ideas about the “security-insecurity” dialectical nexus and securitization as a political technology.The final part summarizes the key points and provisions of the Paris School approach in light of its strengths and flaws. I conclude that the Paris School scholars formulated a new theoretical framework of securitization, which is different from the original version of the theory and based on the different logic of security. The proposed approach is valuable for constructive reflection and critical analysis of security practices that are most common in contemporary neoliberal societies of the West.